2021
DOI: 10.7717/peerj.11910
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNA-target gene regulatory networks in liver fibrosis based on bioinformatics analysis

Abstract: Background Liver cirrhosis is one of the leading causes of death worldwide. MicroRNAs (miRNAs) can regulate liver fibrosis, but the underlying mechanisms are not fully understood, and the interactions between miRNAs and mRNAs are not clearly elucidated. Methods miRNA and mRNA expression arrays of cirrhotic samples and control samples were acquired from the Gene Expression Omnibus database. miRNA-mRNA integrated analysis, functional enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Wang et al [715], Lu et al [716], Shi et al [717], Yu et al [718], Zhang et al [719] and Ren et al [720] reported that altered expression of hsa-mir-3613-3p, hsa-mir-103a-3p, hsa-mir-150-5p, GATA2, RUNX1 and AHR (aryl hydrocarbon receptor) correlated in patients with kidney disease, but these genes might be novel targets for NAFLD. Previous reports have demonstrated that hsa-mir-150-5p [721] and RUNX1 [722] are associated with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 93%
“…Wang et al [715], Lu et al [716], Shi et al [717], Yu et al [718], Zhang et al [719] and Ren et al [720] reported that altered expression of hsa-mir-3613-3p, hsa-mir-103a-3p, hsa-mir-150-5p, GATA2, RUNX1 and AHR (aryl hydrocarbon receptor) correlated in patients with kidney disease, but these genes might be novel targets for NAFLD. Previous reports have demonstrated that hsa-mir-150-5p [721] and RUNX1 [722] are associated with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 93%
“…Among the miRNAs shared by IBD and NAFLD identified in this study, hsa-miR-122-5p has been reported to be a serum marker for the diagnosis of NAFLD ( 61 ), while has-miR-146b-5p is associated with different subtypes of UC ( 62 ). At the same time, hsa-miR-150-5p and hsa-Mir-150-5p were used as the related miRNAs of liver fibrosis ( 63 ). We speculate that has-miR-146b-5p may play a role in the pathogenesis of IBD combined with NAFLD, but this needs to be confirmed by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, the keloid is associated with sex hormone levels, which suggested that expression levels of hsa_circ_0072688 might be regulated by sex hormones. Among miRNAs in the hsa_circ_0072688-centered ceRNA networks, dysregulation of the-miR-146a-5p[38], has-miR-146b-5p [39], hsa-miR-373-3p [40], and hsa-miR-93-5p [41] were reported in organ brosis. KEGG and GO enrichment analysis results demonstrated that hsa_circ_0072688 is related to the extracellular matrix, cell adhesion, cell apoptosis, and stress ber, and is involved in Hippo, Wnt, p53, and SMAD signal transduction.…”
Section: Discussionmentioning
confidence: 99%